Destination Choice, Repeating Behaviour and the Tourist-Destination Life Cycle Hypothesis - Artal-Tur, Andrés (2020)
Repeat visitation is a desired target when managing a destination, which remarks the consolidation of a place as a tourist location and its capacity of attraction. Repeating visitors ensure a stable flow of income, spreading the word on the place advantages, what in turn helps to reduce marketing costs (Choo & Petrick, 2014; Schofield & Fallon, 2012). Some studies reflect that repeater tourists usually show less sensitivity to price and a focus on quality when buying tourism services (Assaker & Hallak, 2012). They can also raise total expenditure and stay duration, given that this type of tourists explore more extensively the destination (Jarvis, Stoeckl, & Liu, 2016; Alegre, Mateo, & Pou, 2011). Repeating behaviour also allow visitors to become familiar with the destination, resulting in higher levels of satisfaction with the vacational experience (Lau & McKercher, 2004).